2008
DOI: 10.1177/0363546508317122
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Concurrent Meniscus Transplantation and Articular Cartilage Repair

Abstract: Combined meniscal allograft transplantation and cartilage restoration offers a safe alternative for patients with persistent symptoms after meniscectomy and focal cartilage injury. Results of combined procedures were comparable to published reports of these procedures performed in isolation. Long-term follow-up is needed to define the survivorship of these procedures in a young patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 43 publications
7
117
1
3
Order By: Relevance
“…The results of patients who undergo combined cartilage repair with meniscal allograft transplantation are equivalent or superior to those reported for cartilage repair as an isolated procedure [25,65]. Rue et al [65] reported a series of 30 patients with combined meniscal allograft transplantation procedures and cartilage restoration procedures. Using various standardized outcome surveys including the Lysholm, International Knee Documentation Committee, and SF-12 scales, these authors demonstrated 76% of patients were completely or mostly satisfied with their surgical results and 90% would have surgery again.…”
Section: Patient Selectionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of patients who undergo combined cartilage repair with meniscal allograft transplantation are equivalent or superior to those reported for cartilage repair as an isolated procedure [25,65]. Rue et al [65] reported a series of 30 patients with combined meniscal allograft transplantation procedures and cartilage restoration procedures. Using various standardized outcome surveys including the Lysholm, International Knee Documentation Committee, and SF-12 scales, these authors demonstrated 76% of patients were completely or mostly satisfied with their surgical results and 90% would have surgery again.…”
Section: Patient Selectionmentioning
confidence: 96%
“…Even partial meniscectomy is associated with increases in tibiofemoral contact forces [42]. The results of patients who undergo combined cartilage repair with meniscal allograft transplantation are equivalent or superior to those reported for cartilage repair as an isolated procedure [25,65]. Rue et al [65] reported a series of 30 patients with combined meniscal allograft transplantation procedures and cartilage restoration procedures.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Most failures (85%) of combined surgery were due to failure of the MAT. Rue et al 200 performed simultaneous combined MAT and cartilage restoration procedures in 31 patients with a symptomatic postmeniscectomy knee with a focal chondral defect. MAT offers a safe alternative for those patients.…”
Section: Results Of Meniscal Transplantsmentioning
confidence: 99%
“…El Attar et al, found a mean failure rate of 10.6% and mean complications rate of 21.3% per trial in their systematic review [7]. Failure has been reported to occur at a mean of 2-3 years [32], 5 years [33], and 11.8 years [17]. The failure rate for medial allograft is higher compared to the lateral allograft [29].…”
Section: Complicationsmentioning
confidence: 99%
“…In general, the results of MAT associated with anterior cruciate ligament reconstruction or cartilage repair/ restoration are not worst compared to isolated MAT [6][7][8]. MAT and associated cartilage procedures (autologous chondrocyte implantation, osteochondral allograft, osteochondral autograft or microfractures) essentially provide similar improvement in pain relief, KOOS score, IKDC score (subjective), Noyes score, Tegner score, and sports level compared to isolated MAT [15,32,34,69,70]. Only Lysholm and modified Cincinnati scores were lower in the combined compared to isolated MAT [71,72].…”
Section: Associated Proceduresmentioning
confidence: 99%